Exercise hemodynamics by echocardiography and right heart catheterization in patients with chronic thromboembolic pulmonary disease. (3rd October 2022) - Dhayyat, A; Mykland Hilde, J; Jervan, O; Stavem, K; Ghanima, W; Melsom, M N; Steine, K
Abstract: Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is an important cause of pulmonary hypertension (PH). A subclinical form of PH is referred to as exercise-induced pulmonary hypertension (EIPH), and its prevalence in patients with chronic thromboembolic pulmonary disease (CTEPD) without pulmonary hypertension at rest is unknown. Purpose: To explore the occurrence of exercise-induced pulmonary hypertension (PH) in patients with CTEPD and compare exercise echocardiography with right heart catheterization (RHC). Methods: In total, 16 patients with CTEPD, all diagnosed after pulmonary embolism, underwent exercise echocardiography and exercise RHC with dynamic supine leg exercise using a cycle ergometer. CTEPH at rest was defined as mean pulmonary artery pressure (mPAP) >20 mmHg and pulmonary vascular resistance (PVR) ≥3WU. EIPH by RHC was defined as mPAP >30 mmHg with total pulmonary resistance (TPR) ≥3 WU. Based on these criteria, our patients with CTEPD are presented by a flow chart (Figure 1). Systolic pulmonary artery pressure by echocardiography was calculated by tricuspid regurgitation peak velocity (TR V max) and the Bernoulli formula: 4 × (TR V) 2 . The RHC examination followed the exercise echocardiography within 2 hours. Groups were compared with independent sample t-test. Results: Four patients (25%) were diagnosed with EIPH by exercise RHC. Patients with EIPH had a mean mPAP at peak exercise of 40.5 mmHg (range 38 to 43mmHg) and TPR of 3.7 WU (range 3.0 to 4.3 WU). The same patients also had a higher TR V max at peak exercise during exercise echocardiography compared to the patients without EIPH (Table 2). None of the patients had signs of elevated left-sided filling pressure during exercise by RHC, and none had left ventricular diastolic dysfunction during exercise by echocardiography. Conclusion: In total, 4 of 16 patients with CTEPD were diagnosed with EIPH. The same four patients also had abnormal pulmonary artery pressure rise during exercise echocardiography and invasive RHC. These findings suggest that exercise echocardiography may be useful for screening patients with CTEPD and suspected EIPH. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Ostfold Hospital Trust